Lipid profile in an urban healthy adult Bangladeshi population (IMC Journal of Medical Science, 2020)
Background and objectives: The prevalence of ischemic heart disease (IHD) has increased in most of the developing countries, including Bangladesh. An important marker of IHD is dyslipidemia which includes high levels of triglyceride (TG), total cholesterol (T-cholesterol), low density lipoprotein cholesterol (LDL-c) and low level of high density lipoprotein cholesterol (HDL-c). So it is very important to know the lipid levels of a particular population for early intervention and prevention of IHD. The present study investigated the lipid levels of healthy urban adult Bangladeshi population.Methods: The cross sectional study was carried out over a period of one year at the Department of Physiology of Ibrahim Medical College, Dhaka, Bangladesh. A total number of 286 apparently healthy individuals were included in this study. Blood sample following overnight fast was collected for determination of serum TG, T-cholesterol, LDL-c and HDL-c. For all four lipid components, 95th percentile value was calculated and compared with values recommended by World Health Organization (WHO).Results: A total number of 286 adult individuals were enrolled of which 130 (45.5%) and 156 (54.5%) were male and female respectively. The mean levels of TG (122±56 mg/dl) and T-cholesterol (178±25 mg/dl) of male participants were significantly (p=0.001, p=0.008) higher than that of females (79.3±35.6 and 170±26 mg/dl). The level of serum HDL-c was significantly (p=0.001) higher in females (46.1±7.8 mg/dl)) compared to the males (39.7±8.6 mg/dl). The 95th percentile values of TG, T-cholesterol and LDL-c were higher than that of values recommended by WHO. Of the total participants, 17.1% to 24.1% had TG, T-cholesterol and LDL-c levels higher than the WHO recommended range.Conclusion: It is concluded that a proportion of our urban healthy young adult population had lipid profiles different from that recommended by WHO.Ibrahim Med. Coll. J. 2020; 14(1): 13-17